O kreśleniu wykresów funkcji wymiernych z użyciem programu Matlab - Janaszak, Tadeusz (Some remarks about the construction of the rational function with the use of Matlab programme, 2009)
The programme Matlab is a magnificent instrument with Matlab is possible to draw the plot of each national function. Many Times in the monitor of the computer is drawn an incomprehensible drawing. In this article is shown a method of study of the function with use of the Matlab
Didactics of Mathematics, 2009, Nr 5-6 (9-10), s. 53-70
Keywords: the national function; diagram of the national function; programme Matlab